Identifikasi Tingkat Kematangan Kelapa Sawit Berbasis Pencitraan Termal - Khusnul Azima; Khairul Munadi; Fitri Arnia; Maulisa Oktiana (Jurnal Rekayasa Elektrika, 2019)
Indonesia is the biggest producer of palm oil (Elaeis guineenis jacq).  The palm tree is a primary commodity that posses a high economic value. Palm oil must be considered in terms of quality to produce optimal and high-quality oil. Previously, the stipulation of the palm tree characterization used manual and visual image utilization method; it may have weaknesses due to the dependency of individual sorting and coruscation factor. Therefore, this research is aimed to improve the performance of the previous method in identifying the ripeness of palm tree based on thermal imaging. The excess of thermal imaging was not related to the coruscation since the level of ripeness was both determined by the temperature and colour. The detection method of this research deployed the colour-based features that are Dominant Colour Descriptor and Color Moment. The DCD  and Color Moment was the input to the K-Nearest Neighbor (KNN) method.  The percentage of identification rate was 89%, and the identification of oil palm maturity level using thermal imaging is more efficient because it is done without human intervention and does not depend on lighting assistance compared to manual method and method of using RGB visual images.